Resonating Within the Dynamo: A Phenomenological Exploration of Work Wellbeing Among Millennials in Jakarta's Startup Ecosystem - Dipoatmodjo, Tenri Sayu Puspitaningsih (Abadi Institute, 2025)
This phenomenological study explores the lived experience of work wellbeing among millennial employees within Jakarta’s dynamic technology startup ecosystem. Through in-depth interviews with ten participants across diverse roles and startup stages, the research reveals that well-being transcends traditional financial metrics, emerging instead as contextualized resonance, a state of thriving within the environment’s inherent chaos, speed, and uncertainty. Four interconnected dimensions define this resonance: (1) Meaningful Contribution (alignment with personal values and tangible impact), (2) Autonomy and Flexibility (trust in self-management, albeit challenged by blurred boundaries), (3) Authentic Interpersonal Relationships (psychological safety and communal support as buffers against stress), and (4) Space for Growth (continuous learning and non-linear development pathways). The findings underscore that millennials derive profound satisfaction from co-creating innovation but require deliberate organizational support to mitigate burnout risks. This study advocates for human-centered HR strategies transforming Jakarta’s startup dynamism from a wellbeing challenge into a catalyst for resilience, retention, and holistic fulfillment.